Clarification of the taxonomic and nomenclatural confusion about Arnica japonica L. f. and A. japonica Thunb. (Asteraceae: Senecioneae) - Li, Cheng-Sheng; Wu, Hai-Song; Fei, Wen-Qun; Ren, Chen (Phytotaxa, 2022)
Arnica japonica L. f. and A. japonica Thunb. have long been controversial about their identities and nomenclature, largely due to the mysterious type material of Arnica japonica L. f. We locate the original material of Arnica japonica L. f., viz., LINN-HS 1322.1, and clarify the misleading description about its leaf form. Arnica japonica L. f. is revealed to be conspecific with A. japonica Thunb. Taxonomic and nomenclatural changes are made accordingly for these two names, and for Gynura japonica and Syneilesis palmata, another two names also involved in this issue. A second-step lectotype of Arnica japonica Thunb. is designated because of the taxonomically mixed material of the original lectotype.